Demokrasi, Agama dan masyarakat Madani - M. Dawam Raharjo (Universitas Islam Indonesia, 1999)
As a worldwide actual issue, nowadays, the consept of civil society has been popular in a lot of countries, especially in Asia, in Latin America Military regihries, and in Europe. In Indonesia, the discussion of the subject has moved into substansial area involving the form of civil society that can be established. There are least three models of the concept: firstly, civil society is only an interim form, because it may be destructed,